Analysis of Indonesia's Economic Resilience in Facing the Global Crisis - Firayani Firayani (Nomico, 2024)
This study aims to analyze Indonesia's economic resilience in facing the global crisis by examining the influence of six main variables, namely the global crisis, fiscal policy, monetary policy, the contribution of the MSME sector, economic growth, and the unemployment rate, this study uses a quantitative approach and multiple linear regression methods, this study utilizes time series data from 2018–2024 processed through Eviews software, the test results show that all variables have a significant influence on national economic resilience, the global crisis and the unemployment rate are proven to have a negative impact, while fiscal policy, monetary policy, MSMEs, and economic growth show a significant positive influence, economic growth is the most dominant variable in strengthening economic resilience, while unemployment is the most weakening factor, this empirical model also indicates that the combination of macro policy instruments and the strength of the domestic sector is the main key in maintaining national economic stability amidst external pressures. This study provides empirical evidence that can be utilized by policy makers in designing resilient and adaptive development strategies, these findings confirm that Indonesia's economic resilience depends not only on short-term responses to the crisis, but also on structural reforms, transparent governance, and cross-sector synergy in economic decision-making.